On the causality between household and government spending on education: A panel analysis across countries - Abida Naurin; Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2021)
This paper sheds light on an important causality which is of primary interest for policy makers, both at country level as well as broad institutional level, though it is largely ignored in the literature. Using panel data from a diversified group of countries and after controlling for various factors and endogeneities within the context of multivariate models, we present evidence that an increase in the intensity of government spending on education leads to an overall increase in the intensity of household spending on education of a roughly equal magnitude, within a span of two years. We further find that the reverse causality does not hold. Specifically, a 1% increase in the intensity of government spending on education induces a contemporaneous increase in the intensity of household spending on education of 3%, followed by a correction of 2% the subsequent year. Our mediation analysis within our set of variables suggests that the causality is only direct, and that there is no statistically significant distinction between low- and high-income countries.
Keywords: E2; G5; I22; 330; Household Spending on Education; Government Spending on Education; Causality; Credit Market